ChemInform Abstract: Proton‐Exchanged Montmorillonite‐Mediated Reactions of Methoxybenzyl Esters and Ethers. Issue 34 (26th August 2014) - Chen, Dongyin; Xu, Chang; Deng, Jie; Jiang, Chunhuan; Wen, Xiaoan; Kong, Lingyi; Zhang, Ji; Sun, Hongbin
Abstract The operationally simple protocol allows the Friedel‐Crafts‐like alkylation of arenes and heteroarenes, as well as the etherification of a variety of alcohols with benzyl acetates.